Design of NS3 VLC module and performance analysis of ad hoc network under VLC and Wi‐Fi layers. (4th July 2018) - Sheikh, Saad M.; Ali, Hamza R.; Asif, Hafiz M.; Baig, Sobia; Khan, Asim A.
Summary: Visible light communication (VLC) is the branch of optical wireless communications that uses light‐emitting diodes for the dual purpose of illumination and very‐high‐speed data communication. The main motivation behind the current work is finding alternatives to the saturated radio frequency spectrum, radio frequency security issue, and vulnerability to interferences. The current work is aimed at developing a module for the physical layer of a VLC‐based ad hoc network in network simulation 3. The VLC physical layer module is developed by using the optical signal modules available in the network simulator. The work also includes modelling of VLC‐based transmitter, wireless optical channel, and the optical receiver. Furthermore, the implementation and evaluation of the VLC‐based physical layer is carried out over a typical ad hoc network under different performance metrics. The designed ad hoc network is also tested under Wi‐Fi module followed by its comparison with corresponding ad hoc network under VLC module. The comparison is based on bit error rate curves, system throughput, and gain in received signal‐to‐noise ratio mainly. Finally, the suitability of different modulation schemes is also investigated in the current work for both Wi‐Fi– and VLC‐based ad hoc networks. Abstract : The current work in the paper shows the efficient performance of VLC‐based physical layer for wireless data transmission over a Wi‐Fi link by implementing a VLC‐based ad hoc network for various modulation schemes and comparing results for different performance metrics like throughput, goodput, and latency. The results clearly reflect the efficiency and effectiveness of VLC link over Wi‐Fi with improved throughput, smaller error rates, and reduced latency.